SMART HOME DESIGN FOR ELECTRONIC EQUIPMENT CONTROL BASED ON INTERNET OF THINGS (IoT) - Dita Nadia Purba (JURNAL TEKNISI, 2025)
Abstract:Â  The advancement of technology, particularly the Internet of Things (IoT), has led to the emergence of smart home concepts that enhance comfort, efficiency, and security for residents. This study aims to design and develop an IoT-based smart home system capable of controlling household electronic devices such as lights, fans, and water pumps via a smartphone. The system employs an ESP32 microcontroller connected to a relay module as the device controller, and the Blynk application as the user interface, enabling remote control through an internet connection. The research methodology includes data collection, needs analysis, hardware and software design, implementation, and system testing. The test results indicate that all devices function properly, respond to commands in real-time, and maintain high stability when connected to the internet. This study serves as a reference for the development of simple, effective, and applicable smart home technology for daily use.Keywords: blynk; ESP32; internet of things (IoT); smart home; remote control.Â Abstract: Perkembangan teknologi, khususnya Internet of Things (IoT), mendorong lahirnya konsep smart home yang mampu meningkatkan kenyamanan, efisiensi, dan keamanan penghuni rumah. Penelitian ini bertujuan untuk merancang dan membangun sistem smart home berbasis IoT yang dapat mengendalikan perangkat elektronik rumah tangga seperti lampu, kipas, dan pompa air melalui smartphone. Sistem menggunakan mikrokontroler ESP32 yang terhubung ke modul relay sebagai pengendali perangkat, serta aplikasi Blynk sebagai antarmuka pengguna untuk kontrol jarak jauh melalui koneksi internet. Metode penelitian meliputi pengumpulan data, analisis kebutuhan, perancangan perangkat keras dan perangkat lunak, implementasi, serta pengujian sistem. Hasil pengujian menunjukkan bahwa seluruh perangkat dapat berfungsi dengan baik, merespons perintah secara real-time, dan memiliki tingkat kestabilan tinggi saat terhubung ke jaringan internet. Penelitian ini memberikan kontribusi sebagai referensi pengembangan teknologi smart home yang sederhana, efektif, dan aplikatif untuk kebutuhan sehari-hari.Keywords : blynk; ESP32; internet of things (IoT); smart home; kontrol jarak jauh.Â